2013
DOI: 10.1063/1.4804383
|View full text |Cite
|
Sign up to set email alerts
|

Detailed consideration of the electron-phonon thermal conductance at metal-dielectric interfaces

Abstract: Articles you may be interested in 3ω-response and energy relaxation times of the electron-phonon system in a metal film Low Temp. Phys. 40, 537 (2014); 10.1063/1.4885062The effect of the electron-phonon coupling on the effective thermal conductivity of metal-nonmetal multilayers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
5
36
1
1
Order By: Relevance
“…Majumdar and Reddy [22] found that the PP interfacial resistance and the volumetric EP resistance in metal are in series. The TBC across TiN-MgO interface they calculated is in agreement with the experimental data measured by Costescu et al [7] Taking a step forward, Singh et al [23] However, there are not many works that consider three channels simultaneously and compare the contributions from different channels. Li et al [24] measured the thermal conduction in periodic Mo-Si multilayers using ω 3 method.…”
Section: Introductionsupporting
confidence: 78%
“…Majumdar and Reddy [22] found that the PP interfacial resistance and the volumetric EP resistance in metal are in series. The TBC across TiN-MgO interface they calculated is in agreement with the experimental data measured by Costescu et al [7] Taking a step forward, Singh et al [23] However, there are not many works that consider three channels simultaneously and compare the contributions from different channels. Li et al [24] measured the thermal conduction in periodic Mo-Si multilayers using ω 3 method.…”
Section: Introductionsupporting
confidence: 78%
“…To determine the size of the error bars, the FDTR-measured phase-lag vs. heating frequency data was fit to the heat diffusion equation to extract the deviations in G when At a metal-dielectric interface, electrons that carry heat within the metal transfer it to phonons that transmit the energy across the interface in a process known as electron-phonon coupling [41]. Electron-phonon coupling has been modeled as a thermal resistance process that is in series with the phonon energy transmission across the interface [42][43][44]. The values of G reported in Figure 2 represent the composite G due to the electron-phonon coupling conductance (G e-p ) and the phonon transmission conductance (G p ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the joint phonon modes exist on both sides of the interface, a part of the energy transferred from electrons to interfacial phonon modes is transferred across the interface. Hence, this conductance relates to direct coupling of electrons to phonons across the interface but is often neglected with the assumption that electrons in metal are thermally insulated from the semiconductor at the interface 5,6,31 .…”
Section: Thermal Conductance Of the Tisi 2 -Si Interfacementioning
confidence: 99%
“…More recently, Singh et al 6 obtained the electron-phonon coupling constant directly from Fermi's golden rule by assuming a deformation potential for electron-phonon scattering. The magnitude of the deformation potential was obtained by fitting to the electrical resistivity of bulk metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation